Reestructuración técnico-administrativa en la empresa Inversiones Heme S.A.S., ubicada en la ciudad de Bogotá D.C. (2019)
This work of degree was developed in the company Inversiones Heme S.A.S., in the city Bogotá D.C, where through an administrative technical restructuring it is sought to improve the productivity of the different management areas of the organization. To achieve this, a diagnosis was carried out to evaluate the internal and external part of the organization and implement strategies that launch their growth. In addition, an operational analysis was performed in order to improve processes at their different stages. As for the administrative part, the strategic planning was improved and a formal structure was given to the organization. Finally, a financial study was carried out to determine the viability of the project.